The Role of Religiosity as a Mediating Variable in the Relationship between Online Transactions and Customer Satisfaction and Loyalty in Islamic Banking - Purnama, Suryari; Sukmasari, Andyani; Bhandari, Rahul (APTISI Transactions on Management (ATM), 2021)
This study aims to determine the role of religiosity as mediation in the relationship between online transactions and customer satisfaction and loyalty in Sharia banking in the Jakarta area. The population of this research is all sharia banking customers in Jakarta. The number of samples in this study was 175 Sharia banking customers in Jakarta by sampling purposive sampling method. The data processing method used is Structural Equation Modelling. The results showed: 1) there is no effect of failure on the experience of online transactions in Sharia banking; 2) there is an effect of service recovery on the customer experience of online transactions in Sharia banking; 3) there is an influence of customer experience on customer satisfaction in online transactions in Sharia banking; 4) there is an effect of customer satisfaction on customer loyalty using online transactions in Sharia banking; 5) customer religiosity moderates between customer experience to satisfaction using online transactions; 6) Customer religiosity moderates the satisfaction of customer loyalty using online transactions in Sharia banking.